Terceirização de serviços públicos e reforma gerencial: o caso Secretaria da Fazenda de Pernambuco - Espírito Santo, Ivanise Hosana do (2010)
The outsourcing is considered a tool of management in modem times. This way of service hiring expands in any work sphere, public or private. In the latter, the economy globalization and the unstoppable competition across the world boost the productivity and optimization of the stages of production, replacing fixed cost by variable cost. In the public sphere, from the decade of 70, the fiscal crisis prevailed in the majority of discussions, suggesting the neoliberal idea of restricting the intervention of the state in the economy in order to contain the public deficit. Emerges the reformist solution of isolating, in a small group, the core business, which is exc1usive and untransferable from the state. By the privatization, one of the reform's axis, the social services are publicizable and the production of goods and public services are delivered to the market. This work focus on the measurement of the result that strategically subsidizes the Department of Finances of Pernambuco state, in terms of finance and administration efficiency, in choosing the most advantageous for the Administration, between hiring effective workers via public exams, in order to realize the supporting activities, or outsourcing.